2013
DOI: 10.1007/s00256-013-1637-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-time sonoelastography of Achilles tendon in patients with ankylosing spondylitis

Abstract: Sonoelastography may be useful for the evaluation of tendon abnormalities in patients with AS; in addition; it may be useful for the evaluation of other inflammatory rheumatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 19 publications
0
52
0
1
Order By: Relevance
“…The best cine-image derived from at least three compression-relaxation cycles was used for the assessment of SE. We have used color-scales and strain ratios for the description of elastographic findings which is defined in the literature [18,20]. In this method, blue and green colors represented hard, whereas yellow and red colors represented intermediate and severely soft tendons, respectively.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The best cine-image derived from at least three compression-relaxation cycles was used for the assessment of SE. We have used color-scales and strain ratios for the description of elastographic findings which is defined in the literature [18,20]. In this method, blue and green colors represented hard, whereas yellow and red colors represented intermediate and severely soft tendons, respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…The strain ratio was calculated by comparing the Achilles tendon to the adjacent fat tissue. The first region of interest (ROI)(A) was placed in the fat tissue as a reference tissue and, the other ROIs(B) were placed in each part of the Achilles tendon [20]. The strain ratio (B/A) was automatically calculated by the sonography machine.…”
Section: Study Populationmentioning
confidence: 99%
“…1). Detailed review of abstracts and full-text reviews resulted in 445 records being excluded and thirteen articles being included in the final analysis [21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Selection and Inclusion Of Studiesmentioning
confidence: 99%
“…On the opposite side, diabetic patients with foot ulcers had thicker but softer tendons than healthy controls and diabetic patients without foot ulcers 41. In patients affected by ankylosing spondylitis, tendon pain was higher in patients with areas of softening. In particular, the distal third was the most commonly affected site and it was commonly associated with both bone erosion and enthesis enlargement 15,42 . Onal et al reported that patients with acromegaly had thicker tendon than healthy subjects, especially in active phase of disease.…”
Section: Other Pathologic Conditions Of the Achilles Tendonmentioning
confidence: 99%